Analysis of Lithuanian aggregate consumption by means of dynamic programming - Jakaitienė, Audronė; Žilinskas , Antanas; Žilinskas , Julius (Lietuvos matematikos rinkinys, 2009)
In the paper, we model household consumption from the perspective of the modern representative agent-based approaches. Household chooses a stochastic consumption plan to maximise the expected value of their time-additive nonlinear utility function subject to asset budget constraint. We apply the dynamic programming for this multi-period problem using the Bellman equation. Beforehand we estimate the structural parameters of the given problem. We employ numerical methods to compute equilibrium. Finally we obtain that observed consumption was just below equilibrium in 2008.